STUDI MULTIKULTURAL PADA ORNAMEN BALI PEPATRAAN: PATRA CINA - FEBRY MAHARLIKA (Serat Rupa: Journal of Design, 2018)
Ornaments are one of the decorative elements that can not be separated from Balinese culture. In addition to decoration, ornaments also contain philosophical content, especially for Hindus in Bali. One type of Balinese ornament is well known is pepatraan. Pepatraan applied to traditional Balinese building by sangging creativity, also obtained from acculturation result between a local culture with other culture that came to Bali, one of them is patra china. Patra china can be found in traditional Balinese buildings as a decorative element placed among other Balinese ornaments. This study describes one of the local cultural products formed by the influence of other nations. A Form of Patra china is described with qualitative interpretative method then attributed to traditional Indonesian archetype. This study also described the history of Patra China, which allegedly originated from China. From the analysis of the form and history of the Patra china, it is concluded that the Patra china is a patra whose basic pattern refers to the pattern of the traditional form of Indonesia, but takes the form Flower Shoes originating from China. The benefit of this research is to developing knowledge about the values contained from patra china ornament as a traditional artwork which created from the process of acculturation of Balinese and Chinese culture.Â Keywords: Bali; multicultural; ornament; patra china